‘Shock Doctrine’ in Indonesia in 2005: Disaster Capitalism in Aceh Post-Tsunami - Asri Wulandhari (Universitas Muhammadiyah Yogyakarta, 2020)
Economy is the most important thing in dealing with problem of individuals, groups, and even a country to meet unlimited needs based on honesty, in accordance with business ethics and prioritizing the public interest. The most ‘loved’ economic system is the capitalist economic system. Capitalists tend to be more principled with economic growth than equality. Even when natural disasters occur, there are some elements who take advantage of the post-disaster conditions. This is called Disaster Capitalism. This research analyzes disaster capitalism occured in Aceh. This paper uses a descriptive analysis method with library research as a data collection techniques. Data collection is analyzed with historical social approach focused to the process of tsunami 2004 and post-tsunami 2005 in Aceh. The result is found that there are some people who ‘exploited’ post-tsunami situation in Aceh, namely transfer of land ownership with the aim of converting oil palm lad on the export market. This project is carried out by Artha Graha Group and its new conglomerate. The solution is from within a country itself. Making the community united and high I solidarity will prevent capitalists from ‘roaming’ into a disaster.